FAKTOR AUDITEE DAN AUDITOR TERHADAP PERGANTIAN AUDITOR - Nanda Agnes Mulyaningsih (2020)
The purpose of this research is to analyze the effect of auditee and auditor factors on auditor turnover. The population used in this research is manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The research sample was selected using the purposive sampling method so as many as 54 manufacturing companies were collected as a research sample. This study uses the Logistic Regression Analysis technique in testing hypotheses and using the help of SPSS versi 25 program to process data. The results of this study indicate that audit opinion has a significant negative effect on auditor turnover, while management change, company growth, and the audit of public accounting firm have no significant effect on auditor turnover.